2015
DOI: 10.1007/s00439-015-1578-x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast model analysis of novel polymerase gamma variants found in patients with autosomal recessive mitochondrial disease

Abstract: Replication of the mitochondrial genome depends on the single DNA polymerase (pol gamma). Mutations in the POLG gene, encoding the catalytic subunit of the human polymerase gamma, have been linked to a wide variety of mitochondrial disorders that show remarkable heterogeneity, with more than 200 sequence variants, often very rare, found in patients. The pathogenicity and dominance status of many such mutations remain, however, unclear. Remarkable structural and functional conservation of human POLG and its S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Because mutations in Polg resulting in deficient polymerase activity can result in mtDNA depletion ( 39 ), we hypothesized that qPCR analysis of mtDNA content from polg −/− zebrafish would reveal a gradual decrease in mtDNA until their death at 3 wpf. Equal amounts of purified DNA were used in order to make comparisons about mtDNA levels between animals and time points, and the difference in Cts for mtDNA and nuclear DNA were calculated to give the dCt.…”
Section: Resultsmentioning
confidence: 99%
“…Because mutations in Polg resulting in deficient polymerase activity can result in mtDNA depletion ( 39 ), we hypothesized that qPCR analysis of mtDNA content from polg −/− zebrafish would reveal a gradual decrease in mtDNA until their death at 3 wpf. Equal amounts of purified DNA were used in order to make comparisons about mtDNA levels between animals and time points, and the difference in Cts for mtDNA and nuclear DNA were calculated to give the dCt.…”
Section: Resultsmentioning
confidence: 99%
“…Comparable phenotypes (the harmful effects observed in yeast reproduce the severity of the phenotypes in humans), the possibility to study variants in heteroallelic states, and easy and fast analysis make budding yeast an excellent model for testing mutations in POLG. In POLG-associated diseases, yeast has enabled researchers to distinguish pathogenic mutations from other single-nucleotide polymorphisms; to show that some polymorphisms may act as phenotypic modifiers; and has demonstrated that certain mutations are not the only cause of a pathology, highlighting the need for further genetic analysis [75][76][77][78][79][80][81].…”
Section: Tnnt2mentioning
confidence: 99%
“…We have grouped together on the server mutations that would result in a putatively non-functional (PNF) POLG. Several of them have been characterized biochemically, corroborating such a non-functional status, though some may retain limited DNA binding capability or other partial functionality [17], [34]. Patients with compound heterozygous PNF mutations that carry the three most commonly reported POLG mutations typically manifest with very severe, infantile onset conditions.…”
Section: Resultsmentioning
confidence: 99%